PELAKSANAAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (CORPORATE SOCIAL RESPONSIBILITY) PT TOBA PULP LESTARI TBK DI BIDANG PENDIDIKAN DAN KESEHATAN TERHADAP MASYARAKAT DESA PANGOMBUSAN KECAMATAN PARMAKSIAN KABUPATEN TOBA SAMOSIR - R. Simanjuntak, Risma; Firdaus, Firdaus; Putri, Adi Tiara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
This research discusses the implementation of corporate social responsibility of PT Toba Pulp Lestari Tbk in the field of education and health to the community of Pangombusan Village, Parm testimonial, Toba Samosir Regency. Corporate Social Responsibility (CSR) is an ongoing commitment from the business community to act ethically and contribute to the economic development of the local community or local community. Based on Article 74 paragraph (1) of the Limited Liability Company Law, hereinafter referred to as UUPT, each company is required to budget and run a CSR program for the environment and the community The community wants the company's existence to contribute to people's welfare. The purpose of writing this thesis, namely; first, to find out how the implementation of PT Toba Pulp Lestari Tbk's corporate social responsibility in the field of education and health to the community of Pangombusan Village, Parmempuan Subdistrict, Toba Samosir Regency, second, to find out what the obstacles of PT Toba Pulp Lestari Tbk in the implementation of corporate social responsibility in the field of education and health for the community of Pangombusan Village, Parm testimonial, Toba Samosir Regency. The type of legal research used by the author is the type of sociological legal research. This research was conducted at PT Toba Pulp Lestari Tbk. Sociological law research uses primary data and secondary data, while the population and sample are parties related to the problem under study, namely the company and the community. Data collection techniques in this study were literature review, interviews and questionnaires. From the results of this study the authors conclude that the implementation of CSR in the field of education and health carried out by the company has not been implemented properly because there are still several programs that have not been implemented optimally. Barriers to the implementation of CSR in the field of education and health experienced by the company is that planning is made sometimes not in accordance with the target, community response, proposals from the community, budget funds. Keywords: Corporate Social Responsibility - Company - Societ